Analysis of Family Support and Levels of Depression HIV/AIDS Patients in Adherence of Antiretroviral Medication in Kediri City - Hanie Kusuma Wardan (Universitas STRADA Indonesia, 2019)
Antiretroviral (ARV) medication adherence is important because ARV can improve quality of live in HIV/AIDS’ patients. Adherence to ARV medication influenced many factors, including family support and levels of depression experienced by patients of HIV/AIDS. The purpose of this research is to analyze the effect of family support and levels of depression patients HIV/AIDS against the ARV medication adherence in Kediri. Research’s design is quantitative research using the approach of cross sectional. The sampling technique used is proportional sampling with cluster random samples as much as 133 respondents who get ARV therapy in Gambiran Hospital, “Pesantren 1” Primary Health Centre, and Seroja Clinic. Data analysis techniques using logistic regression test. The results show that 133 of the respondents, 98 respondents (73.7%) get family support and adherence taking ARV medication, and 99 respondents (74.4%) are not depressed and adherence taking ARV medication. Adherence in this research is referred to take ARV by dosage and by time exactly in schedule. The results of the analysis using logistic regression test shows the value significance of 0.000 < (α = 0.05), meaning that H0 is rejected and the H1 is accepted, this means that there is a relationship of family support and levels of depression HIV/AIDS’ patients against the ARV medication adherence. Family Support and levels of depression HIV/AIDS’ patients affect the ARV medication adherence 80.2%. Conclusion, to get adherence in ARV treatment, HIV’s patient needs family support and get not in depression condition.